PENGARUH ISLAMIC HUMAN CAPITAL TERHADAP KINERJA MANAJERIAL DENGAN PENDEKATAN GUSJIGANG - Dwi Soegiarto (ITB AAS INDONESIA Surakarta, 2022)
The purpose of the study was to explore the entrepreneur's understanding of the human capital based on Gusjigang's business on managerial performance in the Creative Industry in Kudus. Research method: The research strategy used is quantitative research methods. The result of the research is that Human Capital based on Gusjigang has an effect on managerial performance in the Creative Industry in Kudus. The implication of the research is that the Gusjigang Culture strengthens the concept of Islamic Human Capital where in business it is always associated with worship, namely by always remembering Allah SWT, through trade and creation based on Islamic ethical principles.